Formation and tectonic evolution of the khondalite series at the southern margin of the North China Craton: Geochronological constraints from a 1.85-Ga Mo deposit in the Xiong'ershan area - Li, N.; Chen, Yan; McNaughton, Neal; Ling, X.; Deng, X.; Yao, J.; Wu, Y. (Elsevier, 2015)
© 2015 Elsevier B.V. The Taihua Complex is an important metamorphic rock suite at the southern margin of the Trans-North China Orogen and hosts important mineral deposits. Its protolith and metamorphic ages are still controversial. The 1.85-Ga Longmendian Mo deposit in the Xiong'ershan is hosted by the khondalite series of the Duangou Formation, Taihua Complex. Three kinds of rocks are collected for SHRIMP/CAMECA U-Pb dating, including the meta-sedimentary rock that occurred as wallrock, the Mo-mineralized meta-gabbro that intruded the meta-sedimentary rock, and the leucosome that cut both the meta-sedimentary rock and the meta-gabbro. Zircon U-Pb analyses reveal that the precursor of the meta-sedimentary rock was crystallized between 2200 ± 4 and 2742 ± 18 Ma (with most before 2500 Ma), whereas the protolith of the meta-gabbro was formed at 2178 ± 6 Ma. Anatexis zircons in the leucosome yield a weighted mean age of 1943 ± 8 Ma that is indistinguishable with the metamorphic age of the meta-gabbro (1952 ± 4 Ma). In the intensively altered meta-gabbro, hydrothermal titanites were formed by at least two pulses of crystallization at 1940 ± 7 Ma and 1916 ± 9 Ma, respectively. The new data reveal that the khondalite series of the Duangou Formation were formed between 2200 Ma and 2178 Ma. The results are inconsistent with previous subdivision of the Taihua Complex into the Upper Taihua and Lower Taihua Subgroup. Instead, they fit well with the tripartitite divison into the Beizi Group (3.0-2.55 Ga), the Dangzehe Group (2.55-2.3 Ga) and the Shuidigou Group (2.3-2.1 Ga). Compiling zircon U-Pb ages indicate that in the Trans-North China Orogen, the 1.95 Ga and 1.85 Ga metamorphic events are widespread and prominent.